CCL2 and Lactate from Chemotherapeutics-Treated Fibroblasts Drive Malignant Traits by Metabolic Rewiring in Low-Migrating Breast Cancer Cell Lines - Maria Jesus Vera; Iván Ponce; Cristopher Almarza; Gonzalo Ramirez; Francisco Guajardo; Karen Dubois-Camacho; Nicolás Tobar; Félix A. Urra; Jorge Martinez (MDPI AG, 2024)
While cytostatic chemotherapy targeting DNA is known to induce genotoxicity, leading to cell cycle arrest and cytokine secretion, the impact of these drugs on fibroblast-epithelial cancer cell communication and metabolism remains understudied. Our research focused on human breast fibroblast RMF-621 exposed to nonlethal concentrations of cisplatin and doxorubicin, revealing reduced proliferation, diminished basal and maximal mitochondrial respirations, heightened mitochondrial ROS and lactate production, and elevated MCT4 protein levels. Interestingly, RMF-621 cells enhanced glucose uptake, promoting lactate export. Breast cancer cells MCF-7 exposed to conditioned media (CM) from drug-treated stromal RMF-621 cells increased MCT1 protein levels, lactate-driven mitochondrial respiration, and a significantly high mitochondrial spare capacity for lactate. These changes occurred alongside altered mitochondrial respiration, mitochondrial membrane potential, and superoxide levels. Furthermore, CM with doxorubicin and cisplatin increased migratory capacity in MCF-7 cells, which was inhibited by MCT1 (BAY-8002), glutamate dehydrogenase (EGCG), mitochondrial pyruvate carrier (UK5099), and complex I (rotenone) inhibitors. A similar behavior was observed in T47-D and ZR-75-1 breast cancer cells. This suggests that CM induces metabolic rewiring involving elevated lactate uptake to sustain mitochondrial bioenergetics during migration. Treatment with the mitochondrial-targeting antioxidant mitoTEMPO in RMF-621 and the addition of an anti-CCL2 antibody in the CM prevented the promigratory MCF-7 phenotype. Similar effects were observed in THP1 monocyte cells, where CM increased monocyte recruitment. We propose that nonlethal concentrations of DNA-damaging drugs induce changes in the cellular environment favoring a promalignant state dependent on mitochondrial bioenergetics.